1986
DOI: 10.1007/bf01913889
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and calorimetric investigations on crystalline hydrates of barium hydroxide and their deuterated analogues

Abstract: The thermal decompositions of Ba(OH)2.8H20, Ba(OH)z.8D20, Ba(OH)2.H20 and Ba(OH)2. D20 were studied and the phase transitions were identified by DSC and DTA methods. The corresponding enthalpy changes were determined and compared with those calculated from the thermodynamic data. A decrease of the thermal stability was demonstrated for the deuterated crystal hydrates in comparison with the normal ones.The utilization of phase transitions in crystal hydrates as a kind of heat-energy storage explains the particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The temperature of 433.55 K is below the transition temperature 521 K [19,34], which indicated that perhaps the sample was a mixture of solids. However, the experimental enthalpies of solution for reaction (2), at temperatures of (333.55 and 368.15) K, are in excellent agreement with values calculated from ionic additivity using HCl(aq) [16], BaCl 2 (aq) [17] and auxiliary data for H 2 O(l) [18] and the (5)).…”
Section: Calculations and Resultsmentioning
confidence: 99%
“…The temperature of 433.55 K is below the transition temperature 521 K [19,34], which indicated that perhaps the sample was a mixture of solids. However, the experimental enthalpies of solution for reaction (2), at temperatures of (333.55 and 368.15) K, are in excellent agreement with values calculated from ionic additivity using HCl(aq) [16], BaCl 2 (aq) [17] and auxiliary data for H 2 O(l) [18] and the (5)).…”
Section: Calculations and Resultsmentioning
confidence: 99%